Potential for Marine Tourism Development in Kelapa Island, Thousand Islands, DKI Jakarta - Parantika, Asep; Indah Sari, Kelly (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2023)
The Thousand Islands are one of the popular tourist locations nearby Jakarta, Indonesia's capital city. However, it is regrettable that not many people are aware of several locations in the Thousand Islands. Siput Island, which is part of Kelapa Island Village, is a marine tourism destination that not many people know much about or frequently visit. In order to attract tourists, it is therefore vital to promote Siput's tourism industry. Purpose: The study's objectives were to ascertain the current and potential circumstances on the island of Siput, as well as the difficulties and potential strategies for promoting marine tourism there. Methodology: The researcher's method is a qualitative one that includes interviews, observation, and documentation. Data triangulation is the analytical approach employed. Result: The results show that Kelapa Island has advantages in terms of uniqueness and beliefs held by individuals in the local community. The role of MSMEs around the island is also one of the advantages possessed by Kelapa Island. In addition, it was also found that the weakness of Kelapa Island is the lack of available funding for further demolishment. While rivalry, egotism, and natural calamities pose challenges, the potential of Pulau Kelapa is what draws several businesses to invest there. The 4A (Attraction, Accessibility, Amenities, & Ancillary) tourist development strategy for Pulau Kelapa has certain components that have been completed, beginning with attractions in the form of activities and cuisine, while amenities still need to be concentrated on restrooms and places of worship.